What happens in school - Gordon, Violet E. C. (Commonwealth and international library., 1965)
What Happens in School describes school procedure in England and the philosophies which support it. It attempts to tell a story of what really goes on in the schools and to explain, with an extraordinary sensitivity, the curriculum which is thought to be appropriate at each stage. The result is a pen picture of school life which is typical and representative rather than the rule.